Synthesis and Characterisation of Carbon Aerogel Derived from Carboxymethyl Cellulose as a Hydrogen Storage Material - Ahmad Solehi Ab Sabar
A direct, simple, and low-cost approach in synthesising carbon aerogel (CA) composites has been demonstrated in this research through the carbonisation of sodium carboxymethyl cellulose aerogels via sol-gel and freeze-drying processes. Magnesium ions are used as an enhancer for CA among several metal ions including manganese, nickel, and zinc in the preparation step. Magnesium ions shows the best characteristic of CA enhancer as it does not lose during carbonisation at different concentration. The structure and morphology of carbon aerogel-magnesium (CA-Mg) composites are characterised using field emission scanning electron microscopy (FESEM), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and Brunauer- Emmett-Teller (BET) techniques. The ability of CA-Mg composites to act as a hydrogen storage material is analysed using temperature programmed desorption analysis. The FTIR spectra of CA-Mg composites show the completion of carbonisation, because less peak is observed compared to pure CA, as the presence of Mg2+ becomes the main factor in the completion of carbonisation. XRD analysis of CA-Mg composites shows the diffraction peaks of MgO (Periclase) which indicate the generation of MgO during carbonisation process of CA-Mg composites and become the reason for the disappearing of OH peak in the FTIR spectra which means, MgCl2 has been fully decomposed into MgO. Thus, the composites exhibit the characteristic features of CA and MgO. The CA-Mg composites are made up of porous structures with a high specific surface area of 101.4407 m2/g and 0.002 mol of Mg2+ is the optimum concentration for synthesising CA-Mg composites. As a potential candidate for a hydrogen storage material, the CA-Mg composites showed an initial dehydrogenation temperature of 377.22 °C where they desorbed the maximum amount of hydrogen gas at 0.168%. This study emphasises the potential for using CA as a hydrogen storage material, which fulfils the seventh goal of the Sustainable Development Goals (SDG): Affordable and clean energy, as well as Department of Energy (DOE)’s goal of using carbon-based materials